(untitled) (Sustainability in Debate, 2021)
The increased use of water in irrigated rice monocultures in the Jequetepeque Valley, on the northern coast of Peru, has exacerbated environmental, socioeconomic and health problems. The Alternate Wetting and Drying (AWD) irrigation technique aims to increase water management efficiency in rice cultivation. The objective of the present article is to understand farmers’ perceptions about the benefits and risks of implementing AWD. Data from interviews with 319 farmers showed that they recognise nine interactions between AWD’s economic, environmental and health aspects but prioritise economic factors when assessing its benefits. We also identified the main channels and spaces of communication and debate on issues related to agriculture and health that are likely to be effective in promoting the diffusion of AWD. The study demonstrated the relevance of integrated actions to encourage the adoption of agricultural innovations which consider the interactions between environmental sustainability, health issues, and producers’ economic priorities.